Anthraquinone (AQS)/polyaniline (PANI) modified carbon felt (CF) cathode for selective H2O2 generation and efficient pollutant removal in electro-Fenton. (15th February 2022) - Gao, Ying; Zhu, Weihuang; Li, Yaqi; Zhang, Qingyu; Chen, Haonan; Zhang, Jianfeng; Huang, Tinglin
Abstract: A novel binder-free anthraquinone (AQS)/polyaniline (PANI) modified carbon felt (CF) cathode for selective H2 O2 generation and efficient pollutant removal in electro-Fenton was fabricated by CV electro-deposition method. AQS, the oxygen reduction reaction (ORR) catalyst, was immobilized by the PANI film, which contributed to the obtained high stability of the AQS/PANI@CF cathode. The concentration of the electro-generated H2 O2 on AQS/PANI@CF cathode (83.3 μmol L −1 ) was about 10 times higher than that of the bare CF cathode. And the high yield of H2 O2 was attributed to the catalytic reduction of O2 by AQS to generate more superoxide radical (O2 - ), which combined with H + to form H2 O2 . Additionally, the rhodamine B (RhB) degradation efficiency reached 98.8% within 60 min with the AQS/PANI@CF served as the cathode with high stability and good repeatability. The main generated reactive radicals were determined by the quenching experiments and the electron paramagnetic resonance (EPR) tests. Besides, a plausible mechanism of the AQS/PANI@CF cathode applied electro-Fenton process was proposed. This work provided a reliable reference for the subsequent investigations of the binder-free cathode with high performance and stability. Graphical abstract: Image 1 Highlights: A novel anthraquinone/polyaniline coated carbon felt (AQS/PANI@CF) was prepared. The AQS/PANI@CF cathode could enhance the yield of the electro-generated H2 O2 . The AQS/PANI@CF cathode has high performance and stability in electro-Fenton. Mechanism of the AQS/PANI@CF cathode applied in electro-Fenton was proposed.